Factors Associated with Willingness to Choose the Way for Old-Age Care: A Population-Based Cross-sectional Study in Chongqing, China - Rongrong Zhao; Houxiu Zhou; Jingci Zhu (SAGE Publishing, 2021)
The objective of this study is to investigate the factors associated with the willingness for old-aged care and the demands for health care among elders, which might provide a reference for the establishment of health care strategies. A cross-sectional study was conducted via questionnaires among 1553 randomly selected residents aged 65 or older from Chongqing, China during 2016. Data of demographics, and demands for old-age care and health care services were collected. Descriptive analysis was used to examine the characteristics of the respondents. A chi-squared test and multiple logistic regression were performed to explore the relevant factors associated with the preference of old-age care among older people in Chongqing. We found that 85.4% of the respondents were willing to select home-based care: family old age care (55.9%), and its combination form for old-age care: family old age care plus community old age care (29.5%) old age care. Multivariable logistic regression analysis showed that willingness to choose family old age care for old-age care was associated with lower monthly income, more children, worse commercial insurance, better health status, and shorter distance to their children. Most older adults had the demands for health-related services, including regular check-up, regular health seminars, establishment of health files. Hospital was the most acceptable provider for care services, and there was a preference for long-term care and emergency call among the elders. The majority of older Chinese prefer the family old age care and its combination form with community old age care for old-age care, and demand for a variety of health-related services. Home- and community-based care with sound and perfect medical and health mechanism should be the main pattern of old-age care system in China.